Biological Response Modifiers in Combination with Antivirals against Experimentally-Induced Virus Infections - Robert W Sidwell; John H Huffman; Donald F Smee; John Gilbert; Roland K Robins; Meir Kende; John Huggins (Canadian Journal of Infectious Diseases)
Biological response modifiers (BRMs) have particular promise when used in combination with more standard antiviral agents for treatment of viral diseases. Reported here are a series of studies which have used two BRMs in combination with the antiviral drug, ribavirin (l-β-o-ribofuranosyl-1,2,4-triazole-3-carboxamide) in treatment of experimentally-induced phlebovirus (Punta Toro virus) infections in mice. The positive BRMs studied include bropirimine (2-amino-5-bromo-6-phenyl-4[3H]pyrimidinone) given orally at dosages of 25, 50 and 100 mg/kg/day beginning 24 h after virus inoculation. and 7-thia-8-oxoguanosine administered intrapcritoneally at dosages of 6.3, 12.5 and 25 mg/kg/day given 24 and 31 h after virus inoculation. In each experiment. multiple dosages of both BRM and ribavirin were selected to range from ineffective levels to, in certain cases with ribavirin, lethally toxic levels. Ribavirin was always administered orally twice daily for three days starting 24 h after virus inoculation. Both drug combinations were considered synergistic, increasing the therapeutic index compared to either drug used alone, and significantly reducing the evidence of ribavirin toxicity. Efficacy was seen as increased survivors, decreased virus recovery from tissues and blood. and lowered glutamic oxalic and pyruvic transaminase levels in the serum.